Comparison of the Effectiveness of Active and Passive Music Therapy on Echolalia and Pitch Frequency in Children with Level 1 Autism Spectrum Disorder - Ahmadizade, Fahimeh; Mousavi, Said Ali mohammad; Babakhani, Narges (Psychological Research in Individuals with Exceptional Needs, 2025)
Music therapy is a complementary and innovative intervention for children with autism spectrum disorder (ASD), encompassing both active and passive approaches that differ in their implementation methods and potential outcomes. The present study aimed to examine and compare the effectiveness of active and passive music therapy on echolalia and pitch frequency in children with Level 1 ASD. This quasi-experimental study employed a pretest–posttest design with a control group and a two-month follow-up period. The study sample included 33 children aged 4 to 7 years diagnosed with Level 1 ASD, selected through convenience sampling. After meeting the inclusion criteria, participants were randomly assigned to two experimental groups and one control group. The research instruments consisted of the Praat acoustic phonetic software and the Abnormal Behavior Checklist. Data were analyzed using repeated-measures analysis of variance (ANOVA) with SPSS-27 to compare dependent variables across pretest, posttest, and follow-up phases. The results indicated that passive music therapy had the greatest effect in reducing echolalia. Pairwise comparisons with Bonferroni correction showed significant mean differences between the passive and active groups (3.038, p = 0.034) and between the passive and control groups (-4.583, p = 0.001), whereas the difference between the active and control groups was not significant (mean difference = -1.545, p = 0.538). These findings suggest that the passive method was more effective in decreasing echolalia compared to the other groups. Furthermore, the active music therapy group showed a significant improvement in pitch scores compared to the control group. The overall time effect on scores was significant in the multivariate analysis, and the trend of changes varied across groups, although the univariate analysis did not confirm a formal time effect. Passive music therapy showed no significant difference compared to the control condition. Therefore, incorporating music therapy into rehabilitation programs for children with ASD is recommended as a beneficial complementary intervention.